An ecological perspective on living with fire in ponderosa pine forests of Oregon and Washington: Resistance, gone but not forgotten - Merschel, Andrew G.; Beedlow, Peter A.; Shaw, David C.; Woodruff, David R.; Lee, E. Henry; Cline, Steven P.; Comeleo, Randy L.; Hagmann, R. Keala; Reilly, Matthew J. (Trees, Forests and People (Online), 2021)
Wildland fires (WLF) have become more frequent, larger, and severe with greater impacts to society and ecosystems and dramatic increases in firefighting costs. Forests throughout the range of ponderosa pine in Oregon and Washington are jeopardized by the interaction of anomalously dense forest structure, a warming and drying climate, and an expanding human population. These forests evolved with frequent interacting disturbances including low-severity surface fires, droughts, and biological disturbance agents (BDAs). Chronic low-severity disturbances were, and still are, critical to maintaining disturbance resistance, the property of an ecosystem to withstand disturbance while maintaining its structure and ecological function. Restoration of that historical resistance offers multiple social and ecological benefits. Moving forward, we need a shared understanding of the ecology of ponderosa pine forests to appreciate how restoring resistance can reduce the impacts of disturbances. Given contemporary forest conditions, a warming climate, and growing human populations, we predict continued elevation of tree mortality from drought, BDAs, and the large high-severity WLFs that threaten lives and property as well as ecosystem functions and services. We recommend more comprehensive planning to promote greater use of prescribed fire and management of reported fires for ecological benefits, plus increased responsibility and preparedness of local agencies, communities and individual homeowners for WLF and smoke events. Ultimately, by more effectively preparing for fire in the wildland urban interface, and by increasing the resistance of ponderosa pine forests, we can greatly enhance our ability to live with fire and other disturbances.